PEMANFAATAN TEKNOLOGI UNTUK MENDUKUNG PEMBELAJARAN SANTRI PADA PONDOK PESANTREN - Kiki Ahmad Baihaqi; Ahmad Fauzi; Jamaludin Indra (Jurnal Pengabdian Masyarakat Nasional, 2023)
Technology has penetrated all fields, the technology in question is learning media and learning support applications. Especially in the world of Islamic boarding schools, which is religion-based education, so it balances religious education and technological education. With the pandemic, everything in education has changed, namely, what was previously only conventional and face-to-face-based, education that can be done in any condition that breaks the barriers of time and space. So training is needed to optimize the use of online-based learning support media. The training results from 30 out of 35 people successfully completed the training stages and the remaining 5 passed with improvements.